Synthesis and Analgesic Activity of Some Chalcones - Srinivasa Rao, A. (Asian Journal of Chemistry, 2011)
A series of novel 1-(4'-aminophenyl)-3-(substituted aryl/heteroaryl)-2-propen-1-ones (1-16) have been synthesized by treating 4-amino acetophenone with various substituted aromatic and unsubstituted heterocyclic aldehydes in presence of methanol and aqueous alkaline solution at room temperature. Their structures were confirmed by IR, 1H NMR, 13C NMR, EI-MS spectra and elemental analyses data. The synthesized compounds were investigated for their analgesic activity. Compounds 6 and 15 exhibited maximum analgesic activity. Chalcones with electron releasing substituent like amino, hydroxyl, methyl, halogens etc exhibited good analgesic activity.